Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T19:01:48+01:00
A)5y-3x+xy-15=y(5+x)-3(5+x)=(5+x)(y-3)
b)a²+bc+ab+ac=a(a+b)+c(b+a)=(a+b)(a+c)
c)2a²+3b+3a+2ab=2a(a+b)+3(a+b)=(a+b)(2a+3)
d)3x-xy-6y+2y²=x(3-y)-2y(3-y)=(3-y)(x-2y)
e)2a²b²+8a²b-5ab-20a=2a²b(b+4)-5a(b+4)=(b+4)(2a²b-5a)
f)6+2b√3-3a-ab√3=3(2-a)+b√3(2-a)=(2-a)(3+b√3)
2 5 2
  • ewus
  • Początkujący
2009-12-08T19:03:48+01:00
A)5y-3x+xy-15= 5(y-3)-3(x-1)+xy
b)a²+bc+ab+ac=(a+b+c)²
c)2a²+3b+3a+2ab=2a(a+b)+3(a+b)
d)3x-xy-6x+2y²=3(x-2x)-y(x+2y)
e)2a²b²+8a²b-5ab-20a=2a(ab²+4ab)-5(ab+4a)
f)6+2b√3-3a-ab√3=√3(2b-ab)+3(2-a)
1 5 1
2009-12-09T00:42:48+01:00
A)
5y - 3x + xy - 15 = y(5 + x) - 3(5 + x) = (5 + x)(y - 3)
b)
a² + bc + ab + ac = a(a + b) + c(b + a) = (a + b)(a + c)
c)
2a² + 3b + 3a + 2ab = 2a(a + b) + 3(a + b) = (a + b)(2a + 3)
d)
3x - xy - 6y + 2y² = x(3 - y) - 2y(3 - y) = (3 - y)(x - 2y)
e)
2a²b² + 8a²b - 5ab - 20a = 2a²b(b + 4) - 5a(b + 4) = (b + 4)(2a²b - 5a)
f)
6 + 2b√3 - 3a - ab√3 = 3(2 - a) + b√3(2 - a) = (2 - a)(3 + b√3)
1 5 1